Peran Polri dalam Menyelesaikan Perkara Pemakaian Tanah Tanpa Izin dari yang Berhak atau Kuasanya yang Sah - Silaban, Jefriadi; Minin, Darwinsyah; Zul, Muaz (Universitas Medan Area, 2019)
The formulation of the problem in this study is how the authority of investigators to handle cases of land use crime without permission from the rightful or legal authority and how to enforce the law against the land user without the permission of the rightful or authorized attorney in the North Sumatra Regional Police jurisdiction and its obstacles . Then the research method used is descriptive with normative juridical approach. The results of the research at the Directorate of Criminal Investigation of the North Sumatra Regional Police that, who conduct investigations into criminal cases of land users without the permission of the rightful or authorized attorney only at the Directorate of Criminal Investigation of the North Sumatra Police. Based on Article 166 paragraph (3) letter f of the National Police Chief Regulation Number 22 Year 2010 Concerning Organizational Structure and Work Procedures at the Regional Police Level (Polda), Ditsabhara carries out the technical fostering function of maintaining public order in the form of law enforcement of minor criminal offenses and TPTKP. As a result, the case settlement rate is low each year, ranging from 17.56% to 48.7%. This condition can lead to embezzlement of cases (quo vadis) and loss of public confidence in the performance of the North Sumatra Regional Police Directorate General Criminal Investigation.